Transcriptomic Changes in Osteoblasts Following Endothelial Cell‐Cocultivation Suggest a Role of Extracellular Matrix in Cellular Interaction. Issue 8 (21st January 2016) - Lampert, Florian M.; Simunovic, Filip; Finkenzeller, Günter; Pfeifer, Dietmar; Stark, G. Björn; Winninger, Oscar; Steiner, Dominik
ABSTRACT: Vascularization is important for bone development, fracture healing and engineering of artificial bone tissue. In the context of bone tissue engineering, it was shown that coimplantation of human primary umbilical vein endothelial cells (HUVECs) and human osteoblasts (hOBs) results in the formation of functional blood vessels and enhanced bone regeneration. Implanted endothelial cells do not only contribute to blood vessel formation, but also support proliferation, cell survival and osteogenic differentiation of coimplanted hOBs. These effects are partially mediated by direct heterotypic cell contacts. In a previous report we could show that cocultivated hOBs strongly increase the expression of genes involved in extracellular matrix (ECM) formation in HUVECs, suggesting that ECM may be involved in the intercellular communication between hOBs and HUVECs. The present study aimed at investigating whether comparable changes occur in hOBs. We therefore performed a microarray analysis of hOBs cultivated in direct contact with HUVECs, revealing 1, 004 differentially expressed genes. The differentially expressed genes could be assigned to the functional clusters ECM, proliferation, apoptosis and osteogenic differentiation. The microarray data could be confirmed by performing quantitative real time RT‐PCR on selected genes. Furthermore, we could show that the ECM produced by HUVECs increased the expression of the osteogenic differentiation marker alkaline phosphatase (ALP) in hOBs. In summary, our data demonstrate that HUVECs provoke complex changes in gene expression patterns in cocultivated hOBs and that ECM plays and important role in this interaction. J. Cell. Biochem. 117: 1869–1879, 2016. © 2016 Wiley Periodicals, Inc. Abstract : We performed a microarray analysis of human osteoblasts (hOBs) cultivated in direct contact with HUVECs to scritinize their intercellular communication in more detail with specific focus on the extracellular matrix (ECM). The differentially expressed genes could be assigned to the functional clusters ECM as well as proliferation, apoptosis and osteogenic differentiation; the results were confirmed by PCR and functional assays. In summary, our data demonstrate that HUVECs provoke complex changes in gene expression patterns in cocultivated hOBs and that ECM plays and important role in this interaction.